2015
DOI: 10.7150/jca.9591
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miRNA3195 and miRNA374b Mediates the Anti-Angiogenic Properties of Melatonin in Hypoxic PC-3 Prostate Cancer Cells

Abstract: Recently microRNAs (miRNAs) have been attractive targets with their key roles in biological regulation through post-transcription to control mRNA stability and protein translation. Though melatonin was known as an anti-angiogenic agent, the underlying mechanism of melatonin in PC-3 prostate cancer cells under hypoxia still remains unclear. Thus, in the current study, we elucidated the important roles of miRNAs in melatonin-induced anti-angiogenic activity in hypoxic PC-3 cells. miRNA array revealed that 33 miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 42 publications
4
79
0
Order By: Relevance
“…In relation to this point, an investigation of the anti-angiogenic effects of melatonin on hypoxic PCa PC3 cells identified a melatonindependent increase in the expression of miR-374b. Subsequent studies confirmed that miR-374b mediated the anti-angiogenic effects of melatonin by inhibiting VEGF expression (Sohn et al 2015).…”
Section: Post-transcriptional Regulation Of Vegf Signaling In Pcamentioning
confidence: 59%
“…In relation to this point, an investigation of the anti-angiogenic effects of melatonin on hypoxic PCa PC3 cells identified a melatonindependent increase in the expression of miR-374b. Subsequent studies confirmed that miR-374b mediated the anti-angiogenic effects of melatonin by inhibiting VEGF expression (Sohn et al 2015).…”
Section: Post-transcriptional Regulation Of Vegf Signaling In Pcamentioning
confidence: 59%
“…Melatonin inhibition of HIF1α signaling and reactive oxygen species generation has also been established (Cho, et al 2011; Park et al 2009; Paroni, et al 2014). Several microRNA (miRNA)s including miR3195 and miR374b were significantly up-regulated while other miRNAs were down-regulated in melatonin-treated cells under hypoxia compared to untreated control (Sohn, et al 2015). In addition to hypoxia and androgen deprivation, melatonin also seems to sensitize CaP cell lines to cell death under hypoglycemic conditions (Gobbo, et al 2015; Kabasakal, et al 2011).…”
Section: Melatonin Regulation Of Prostate Carcinogenesismentioning
confidence: 99%
“…However, the mechanisms of melatonin's antiangiogenic in any tumor including NSCLC are still unclear. Numerous studies have documented that melatonin exhibits antiangiogenic actions, in part, by downregulating VEGF and HIF-1α in several cancers via different mechanisms; the cancer types included breast [16, 149], prostate [150152], colon [153, 154], liver [155], and pancreatic cancer [156, 157]. These studies may provide reference for the future work in the NSCLC research field.…”
Section: Potential Directionsmentioning
confidence: 99%